(untitled) (Research, Society and Development, 2022)
This study is based on the discussion of reverse logistics applied to the process of solid waste, especially plastic (PET), with a view to understanding and promoting the theme of the importance of recycling, where it was decided to use in its methodology, theoretical reference on the theme as well as the application of a survey for a better understanding in the view of the interviewees. It appears that there is still much to be discussed on the subject, whether through public agencies or society as a whole, as well as the use of good practices for the reverse logistics process of these wastes in the search for better environmental awareness.